Advocacy for children with epilepsy: Leveraging the WHA resolution. Advocacy Task Force, Commission of Pediatrics, International League Against Epilepsy. Issue 2 (14th May 2018) - Wilmshurst, Jo M.; Guekht, Alla; Secco, Mary; Helen Cross, J.; Perucca, Emilio
Summary: In May 2015 the World Health Assembly (WHA) approved the Resolution on the Global Burden of Epilepsy. This report addresses how the Resolution can be leveraged to improve the care of children with epilepsy worldwide. Children with epilepsy have unique needs and face unique challenges from stigma at all levels of society. Children lack a voice to lobby for their own needs, including their right to have access to education. Effective leadership and governance should be enhanced through the support of stakeholders empowered to counsel, advise, and lobby for appropriate care. National health care plans should integrate primary and specialist care, and they need to be adapted to local specificities. Antiepileptic medicines should be widely accessible in appropriate, sustained, and affordable ways. Public awareness initiatives are needed to improve the inclusion of affected children in society and to reduce stigma. Cost‐effective interventions are also needed to address preventable causes of epilepsy. Without greater investment in research, evidence‐based interventions cannot be implemented. Through all of this, civil society must be engaged to ensure that the multivariate dimensions from the clinic to the community are addressed to fulfil the needs of children with epilepsy.